General algorithm for efficiency evaluation of multi-column distillation flowsheets; Petroleum and Coal; Vol. 60, iss. 5 - Samborskaya M. A. Marina Anatolievna; Gryaznova I. A. Inga Andreevna; Volf A. V. Andrey Viktorovich; Popok E. V. Evgeniy Vladimirovich (2018, 2018)
Title screen